Conquistas socioculturais dos povos indígenas brasileiros: uma luta histórica - Santos, Adreana Peruzzo dos (2013)
In Brazilian society, Indians are getting historically stronger principally since constitutional achievements in 1988. These conquests came from Indigenous peoples struggle and the strength of organizations towards the permanence of Indigenous values and cultural traditions. However, it is still noticed that most Brazilian people, especially the educators, have a stereotyped view about Indians, considering them exotic and savage and this was perpetuated by European colonizers since the very beginning of Brazilian colonization. In order to break with this stereotyped conception, the Indian on this paper is conceived as a citizen that conquered the right to spread his proper way of life, cultures and values. Due to this scenario, this paper aims to discuss the conquest of Indigenous peoples’ social and cultural autonomy in non-indigenous societies, specifically from the insertion of Indigenous schooling in the national education system and propagation of Indigenous cultures through Indigenous people written literature. The bibliographic basis behind this work are supported by official documents from Federal level about indigenous and studies: on Indigenist and Indigenous policies presented by Gomes (2012), Munduruku (2012), Freire (2006) and Luciano (2006); on Indigenous education and schooling emphasized by Kaingang (2004), Munduruku (2010) and Yamã (2007); and on Indigenous literary representation shown by Alencar (1991), Andrade (1978) Gonçalves (1997), Moura (2009), Tabajara (2009), Tiago (2009) and Graúna (2009).